Coronary Artery Anomalies in D-Transposition of the Great Artery Following Arterial Switch Operation - Thita Pacharapakornpong (2022)
Background: The survival rate of patients following arterial switch operation (ASO) exceeds 95%, but coronary artery anomalies (CAA) contribute to a 2% incidence of sudden cardiac arrest later in life. Therefore, we aimed to assess abnormal findings of coronary arteries in post-ASO patients. Methods: Coronary computed tomography angiography (CCTA) is performed on post-ASO patients who meet institutional criteria. Intraoperative findings of coronary artery patterns were retrospectively reviewed and categorized using the Leiden classification system. Coronary artery anomalies were detected by CCTA and associations with coronary artery compromise were explored. Results: Forty-three patients who had CCTA with a median age of 15.6 years (12–21.3 years) were included in the study. Unusual coronary patterns were identified in 20 (46%) patients before ASO. CCTA identified 25 CAA in 22 patients (eleven with prepulmonic course, nine with interarterial course, three with acute take-off angle, and two with significant stenosis). Postoperative CAA was more common in patients with unusual coronary patterns (90% vs. 17.4%; p < 0.001). Nine patients experienced chest pain and two patients required coronary artery bypass graft. A common ostium of RCA and LAD or LMCA were associated with significant chest pain (OR 14.3%, 95% CI 2.5 to 82.3). Conclusions: Coronary artery anomalies in post-ASO are common. All post-ASO patients should have coronary artery imaging before participating in competitive sport and when they reach adolescence. Patients with unusual preoperative coronary artery patterns should undergo coronary artery imaging when feasible. Follow-up imaging studies are indicated in patients with post-operative coronary artery abnormalities.